Identification of Learning Obstacles on Surface Area of Cube and Cuboid for Junior High School Students - Trysa Gustya Manda; Jarnawi Afgani Dahlan; Dadan Afgani Dasari (JURNAL EKSAKTA PENDIDIKAN (JEP), 2025)
Background of this research was the fact that there are still many students of class VIII SMP N 24 Padang who has learning obstacles in the process of learning mathematics, especially in the field of geometry. The learning obstacles experienced by students were identified through a preliminary study and analysis of learning obstacle identification tests on area of ​​cubes and cuboids, and interviews with class teachers and students. The types of learning obstacles in this study are ontogenic obstacles, didactical obstacles, and epistemological obstacles. The design of this study used a descriptive qualitative research method with learning obstacle identification test instruments on area of ​​cubes and cuboids, and interviews. The subjects of this study were class VIII students of SMP N 24 Padang who took the test and interviews, and mathematics teachers as interview respondents. The results of this study identified learning obstacles consisting of ontogenic obstacles, didactical obstacles, and epistemological obstacles